Connotative Meaning in the “Four” Album by One Direction - Risma Rahmawati; Ida Zuraida Supri (Budapest International Research and Critics University, 2023)
This research aims to identify the words containing connotative meanings based on the context and to analyze the types of connotative meanings in the “Four” album by One Direction. This research uses the qualitative descriptive method. The steps of collecting the data are reading, identifying, categorizing, analyzing the data containing connotative words, and finally, drawing the conclusion. The theory of connotative meaning and types of connotative meaning is based on the theory proposed by Leech (1974). The results of this research show that there are 49 connotative words found in the “Four” album by One Direction. The words containing connotative meanings are categorized into 3 types of connotative meanings. All three types of connotative meanings found are as the following distribution: 22 (45%) data for negative connotative meanings, 19 (39%) data for positive connotative meanings, and 8 (16%) data for neutral connotative meanings. In conclusion, the dominant types of connotative words found in the “Four” album by One Direction have negative connotative meanings.